Ampel-Monitor Energiewende: Ambitionierte Ziele, aber zu geringe Dynamik - Wolf-Peter Schill; Alexander Roth; Adeline Guéret; Felix Schmidt (Wirtschaftsdienst, 2024)
– The German "traffic light" (Ampel) coalition has set ambitious new energy transition targets. Using an open data tool developed at DIW Berlin, we discuss the progress and challenges of selected indicators. Since the government took over, photovoltaic capacity increased by 45 % to 87 GW by April 2024, with a planned doubling by 2030. However, onshore wind power grew by only 11 % to 62 GW. The installation rates of heat pumps and electric vehicles are also insufficient to reach the 2030 targets of six million and 15 million, respectively. Currently, only about 1.8 million heat pumps and 1.5 million electric cars are in use. Accelerated efforts and policy measures are necessary to achieve the energy transition goals, focusing on strategic planning and implementation.
Keywords: Q40; Q42; Q48; 330; Energiepolitik; Energiewende; Deutschland; Energiepolitik; Energiewende; Deutschland